Mountain Literature: Mount Everest in the eyes of the two Nepalese Climbers - Gautam, Pragya (Voice of Teacher, 2021)
This article looks at the Mountain Literature of Nepal, based on the writings of two Nepalese mountaineers of Mount Everest, Jamling Tenzing Norgay, and Lhakpa Phuti Sherpa. It presents their feelings, observations, and the challenges they faced while climbing up the peak. The Humans’ appetite for travelling, their spirit of adventure and exploration, and their desire to know and conquer the unknown have inspired many to climb the mountains. Though Mountaineering is a daring adventure, many climbers are attracted to it. The mountaineers try to test their courage and stamina. For that, they risk their lives in snow, bone-chilling avalanche, and sharp windy weather to reach the summit. They know that getting the pinnacle is not always easy, but it is worthwhile. The magic of Mount Everest attracts the attention of the mountaineers. Its beauty, mystery, and majesty make Nepal, a center of attraction. For all, the mountains are the abode of Gods and Goddesses. They are the sources of peace, happiness, power, faith, and enlightenment. The Mountaineering narratives have contributed much to the development of Nepalese mountain literature. It is a rich source of information, that is beneficial not only for the Mt. Everest climbers but also for the lover of mountains.